Rare case of intrauterine device rectal migration revealed by lower GI bleeding: A case report and literature review - Amal Hassini, MD; Ghizlane Kharrasse, MD; Kaouthar Rais, MD; Maissae Rahaoui, MD; Fatima Adamou Mainassara, MD; Abdelkrim Zazour, MD; Hajar Koulali, MD; Ouiam Elmqaddem, MD; Zahi Ismaili, MD (Radiology Case Reports)
Rectal migration of an intrauterine device (IUD) is a rare but potentially serious complication requiring prompt diagnosis and management. We present a rare case of rectal migration of an intrauterine device (IUD) in a 26-year-old female, highlighting the clinical presentation, diagnostic evaluation, laparoscopic removal, and postoperative outcomes. This case emphasizes the critical importance of vigilant monitoring, early intervention, and close follow-up in managing IUD migration to ensure optimal patient outcomes. Timely recognition and intervention resulted in successful symptom resolution and a favorable long-term prognosis.